Increasing Maternal Knowledge on Childhood Stunting and Gastrointestinal Disorders - Athiyyah, Alpha Fardah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Stunting is a condition associated with inadequate nutrition and frequent illnesses during the first 1000 days of life. Diarrhea and helminthic infection were prevalent risk factors for stunting in children under five years of age. In 2017, Bondowoso was being one of the regency exhibiting the elevation rates of stunting. Stunting prevalence in Curahdami District, Bondowoso found up to 70% in 2018. This study aimed to identify the effect of the community development on maternal knowledge in Curahdami District, Bondowoso about stunting and gastrointestinal disorder. The community development was consisted of educational event and anthropometry measurement. The maternal knowledge was measured using pre and post-test design. Thirty-seven children were measured, and over half exhibited stunting; maternal knowledge considerably improved before and after the educational intervention. In conclusion, the community development through educational sessions has successfully enhanced maternal awareness in Curahdami District, Bondowoso which could become a regular program in the future.